The Classification, Prenatal Diagnosis and Perinatal Treatment of Fetal Lingual Lesions - Shuangping Liu; Mingxing Zhang; Qiongjie Zhou; Yu Xiong; Jue Li; Yang Pan (Maternal-Fetal Medicine)
Abstract. Fetal lingual lesion is a rare category of embryological anomalies, characterized by distinctive anatomical positioning, which may precipitate mechanical airway obstruction to unfavorable perinatal outcomes. There is a lack of comprehensive prenatal diagnostic strategies and effective treatments. This review has conducted a systematic literature overview of the clinical classification of fetal lingual anomalies, prenatal diagnosis, and perinatal treatment, including prenatal ultrasonography and magnetic resonance imaging, for optimizing perinatal care and obtaining an improved pregnancy outcome. Utilizing a multidisciplinary team framework, individualized peripartum management strategies are developed, contingent upon the presence or absence of airway compromise, with selective application of the ex-utero intrapartum treatment procedure as clinically warranted. By refining diagnostic accuracy and advancing therapeutic protocols, this review aims to elevate clinical management standards for congenital lingual lesions, thereby enhancing both short-term perinatal outcomes and long-term developmental prognoses.